PUPILS’ RIGHTS AND RESPONSIBILITIES IN CONFLICTS BETWEEN PUPILS AND TEACHERS - Čiuladienė, Grazina; Kairiene, Brigita; Sinkevič, Edita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This paper aims to reveal students' reactions to a conflict situation due to the nonimplementation of students' rights and duties. The data was collected by the means of a questionnaire (anonymous survey). The participants of the study were 241 pupils of a general education school (grades 5-8). The data show that conflicts between pupils and teachers are a daily occurrence. Conflicts between pupils and teachers arise from teacher‘s behaviour that ignores or violates pupil‘s rights: when the teacher explains the subject in an uninteresting way (60.2%); when teacher assigns too many tasks for pupils (58.9%); expresses negative bias towards the pupil (34.4%); teacher restricst pupil‘s independence (34.4%); teacher ignores the pupil‘s abilities (29.4%); teatcher does not assist the pupil (22%); teacher discriminates against the pupil (14.9%); or teacher behaves rudely towards the pupil (13.2%). The survey revealed that pupils tend to be passive during conflicts with the teacher: 47.8% of the pupils chooses avoidance strategy, 52.3% adapt, 29.9% of the pupils chooses the strategy of indirect protest, 6.6% of the pupils chooses direct aggression tactics (saying something offensive, refusing to do the task, etc.). Correlation analysis shows that conflict is most likely to occur when the teacher penalises pupil‘s misbehaviour through grading, when the teacher fails to notice the pupil‘s efforts, and when the teacher fails to help the pupil. As the teacher is the one who is responsible for building the pupil-teacher relationship, the teacher must take the lead in fostering a relationship of dignity and respect with the pupil by exercising his/her rights and resolving conflicts in a constructive way.